Cytogenetic markers as a tool for characterization of hybrids of Astyanax Baird & Girard, 1854 and Hyphessobrycon Eigenmann, 1907 - Goes, Caio Augusto Gomes [UNESP]; Daniel, Sandro Natal [UNESP]; Piva, Lucas Henrique; Yasui, George Shigueki; Artoni, Roberto Ferreira; Hashimoto, Diogo Teruo [UNESP]; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP] (Pensoft Publishers, 2020)
Astyanax Baird et Girard, 1854, is one of the largest genera in the family Characidae and comprises 177 valid species. This genus has been the focus of cytogenetic studies primarily owing to the presence of B chromosomes and high karyotypic diversity among different populations. The intense genetic variability in Astyanax is one of the factors responsible for the occurrence of species complexes, which are groups (1) with certain difficulties in establishing common genetic pools or (2) belonging to different cryptic species. To evaluate cytogenetic marker inheritance and the possibility of the identification of these hybrids, this study aimed to describe cytogenetic hybrids from three strains of species of the genera Astyanax and Hyphessobrycon Eigenmann, 1908. A. lacustris Lutken, 1875, A. schubarti Britski, 1964, A. fasciatus Cuvier, 1819, and H. anisitsi Eigenmann, 1907 were used to generate three hybrid lineages. The diploid number, heterochromatin sites, and ribosomal genes (18S and 5S rDNA) of the parental strains and the hybrids were analyzed. The results indicated that the three hybrid lineages had cytogenetic markers of both parents, presenting Mendelian inheritance. However, differences in distribution of heterochromatic blocks were observed between the hybrids and the parent strains. Our results allowed the identification of the hybrid strains based on the cytogenetic markers applied, reinforcing the efficiency of cytogenetic markers as tools for identification and indicating that such events may increase the karyotypic diversity in the genera Astyanax and Hyphessobrycon.
Keywords: B chromosomes; Chromosome polymorphism; Neotropical fishes; Repetitive DNAs; Species complex